Membrane reactors for hydrogen production processes - De De Falco, Marcello; Marrelli, Luigi; Iaquaniello, Gaetano (Springer, 2011)
Membrane Reactors for Hydrogen Production Processes deals with technological and economic aspects of hydrogen selective membranes application in hydrogen production chemical processes. Membrane Reactors for Hydrogen Production Processes starts with an overview of membrane integration in the chemical reaction environment, formulating the thermodynamics and kinetics of membrane reactors and assessing the performance of different process architectures. Then, the state of the art of hydrogen selective membranes, membrane manufacturing processes and the mathematical modeling of membrane reactors are discussed. A review of the most useful applications from an industrial point of view is given. These applications include: natural gas steam reforming, autothermal reforming, water gas shift reaction, decomposition of hydrogen sulphide, and alkanes dehydrogenation. The final part is dedicated to the description of a pilot plant where the novel configuration was implemented at a semi-industrial scale. Plant engineers, researchers and postgraduate students will find Membrane Reactors for Hydrogen Production Processes a comprehensive guide to the state of the art of membrane reactor technology.